2010
DOI: 10.1149/1.3481601
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lanthanide Precursors as Dopants for Advanced High-k Materials

Abstract: In an effort to replace SiO2 as a gate dielectric, many high-k materials are under evaluation. Rare earth oxides have demonstrated potential to be used as dopants in electronic devices such as gate oxides in CMOS transistors or in DRAM trench capacitors. This interest is motivated by their relatively high-k value and their compatibility with silicon. This work evaluated several lanthanide precursors by TGA and DSC to determine their thermal properties and select promising molecules to be tested in atomic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 13 publications
(15 reference statements)
2
9
2
Order By: Relevance
“…) 3 observed here is higher than that reported previously (250 °C) 33 and is higher than the ∼330 °C value reported for Pr(C 5 H 4 Et) 3 . 31 The TGA trace conducted under a nitrogen atmosphere showed a single step weight loss (Figure S1), with <10% nonvolatile residue at 500 °C, consistent with the earlier report.…”
Section: ■ Results and Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…) 3 observed here is higher than that reported previously (250 °C) 33 and is higher than the ∼330 °C value reported for Pr(C 5 H 4 Et) 3 . 31 The TGA trace conducted under a nitrogen atmosphere showed a single step weight loss (Figure S1), with <10% nonvolatile residue at 500 °C, consistent with the earlier report.…”
Section: ■ Results and Discussioncontrasting
confidence: 77%
“…The thermogravimetric analysis (TGA) of Pr(C 5 H 4 iPr) 3 indicated that it is more volatile than Pr(C 5 H 4 Et) 3 and PrCp 3 . 33 The ALD growth of Pr 2 O 3 was reported by using Pr(C 5 H 4 iPr) 3 and ozone at 200−250 °C. 33 The growth rate was 0.4 Å/cycle between 200 and 250 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,73 Finally, the ALD growth of Pr 2 O 3 films using Pr(C 5 H 4 iPr) 3 and ozone showed an ALD window from 200 to 250 °C, suggesting that not all lanthanide cyclopentadienyl precursors have high upper temperature limits for self-limited growth. 74 Precursors containing alkoxide, bis(trimethylsilylamide), and amidinate ligands have been evaluated as precursors for the growth of lanthanide oxide films but exhibit problems that include lack of self-limiting growth, low decomposition temperatures, variable reactivity toward water, and impurity incorporation in the films. 29 Precursors containing new ligands such as guanidi-nate 40 and malonate 29 are promising.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the close similarity of the p K a values for water (p K a = 14.00, 15.7) and cyclopentadiene (p K a = 16) may lead to a low reactivity of lanthanide cyclopentadienyl precursors with water in oxide growth. Moreover, the ALD growth of some lanthanide cyclopentadienyl precursors with water does not exhibit self-limited growth. , Finally, the ALD growth of Pr 2 O 3 films using Pr­(C 5 H 4 iPr) 3 and ozone showed an ALD window from 200 to 250 °C, suggesting that not all lanthanide cyclopentadienyl precursors have high upper temperature limits for self-limited growth . Precursors containing alkoxide, bis­(trimethylsilylamide), and amidinate ligands have been evaluated as precursors for the growth of lanthanide oxide films but exhibit problems that include lack of self-limiting growth, low decomposition temperatures, variable reactivity toward water, and impurity incorporation in the films .…”
Section: Resultsmentioning
confidence: 99%